Red-light photobiomodulation improves cognition and neuropsychiatric symptoms in post-stroke cognitive impairment: a randomized trial - Huang, Xuerong; Sun, Zihui; Wu, Weijie; Lou, Linli; Wang, Panpan; Wang, Qin; Fu, Yuanyu; Xu, Liange; Song, Mengwan; Zhu, Lidong; Huang, Jin; Ni, Shaobo; et al. (Frontiers in Neurology, 2025)
IntroductionAcute stroke patients often develop post-stroke cognitive impairment (PSCI) and dysthymic disorders. Formaldehyde (FA) induces cognitive decline and depression; while red light (RL) at 630 nm can degrade FA by activating FA-dehydrogenase (FDH). This study investigates the therapeutic effects of a novel RL device on cognitive function and neuropsychiatric symptoms in patients with PSCI.MethodsThis was an exploratory, parallel-group, randomized controlled trial with concealed allocation, assessor blinding and intention-to-treat analysis. Stroke patients (n = 90) were enrolled. A total of 38 patients in the PSCI group and 44 patients in the PSCI-RL group completed the study. Participants were followed for 6 months, during which the intervention phase comprised 3 months of RL therapy or sham stimulation, followed by continued follow-up. Cognitive [Montreal Cognitive Assessment (MoCA)/Mini-Mental State Examination (MMSE)], neuropsychiatric [Hamilton Depression Rating Scale (HAMD), Hamilton Anxiety Rating Scale (HAMA)], and functional [Barthel Index (BI)] assessments were conducted at baseline and 6 months. Blood and urine levels of key enzymes and metabolites involved in FA metabolism were quantified, including semicarbazide-sensitive amine oxidase (SSAO, an FA-generating enzyme), FDH (an FA-degrading enzyme), cytochrome c (Cyt-c), FA, hydrogen peroxide (H2O2, a marker of FA generation), and coenzyme Q10 (CoQ10, an endogenous FA scavenger).ResultsThe phototherapy device improved cognitive abilities, reduced anxiety and depression, lessened stroke severity, and enhanced daily living activities in the PSCI-RL group at 6 months. Additionally, RL therapy altered FA metabolism, as it lowered SSAO and H2O2 levels and increased FDH, Cyt-c, and CoQ10 in blood and/or urine of PSCI patients.ConclusionsRL therapy may improve clinical symptoms in post-stroke patients by modulating FA metabolism, suggesting a safe and promising approach for treatment and rehabilitation.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=159956, Identifier: ChiCTR2200058991.